Enhanced in vivo tumour imaging by EDTA-bis-GNGR functionalized core shell CdSe:ZnS quantum dot: synergistic effect of active passive targeting. Issue 16 (2nd February 2016) - Mathur, Rashi; Bag, Narmada; Varshney, Raunak; Hussain, Firasat; Kaul, Ankur; Kumari, Neelam; Chauhan, Ramprakash; Singh, Shivani; Singh, Sweta; Mishra, Anil. K.
Abstract : Use of QD-homodimeric system enhances tumour targeting due to the synergistic effect of active passive targeting. Abstract : It has been shown in one of our earlier studies that the homodimeric N2 S2 system enhances the biocompatibility of semiconductor core shell CdSe:ZnS quantum dots by lowering their toxicity and optimizing the steric ligand packing density. In this study we functionalize the core shell quantum dots with the same homodimeric ligand and add two moieties of GNGR (Gly-Asn-Gly-Asp) peptide which contain the NGR motif known to target the CD13 receptors in tumour vasculature. The aim is to study the influence of active receptor based targeting by peptide and passive targeting by QD nanoconjugate on tumour imaging. The core shell CdSe:ZnS quantum dot were synthesised and conjugated with EDTA-bis-GNGR ligand. The docking studies show high binding affinity of the synthesised quantum dot nanoconjugate to the CD13 receptor. The GNGR peptide was synthesised on solid phase using Fmoc chemistry, followed by its conjugation to EDTA-bis-cysteamine. The complete physicochemical characterisation of the ligand was done using 1 H NMR, 13 C NMR and mass. The comparative in vivo kinetics, biodistribution and tumour targeting by native GNGR, EDTA-bis-GNGR and EDTA-bis-GNGR-QD was studied in murines after radiolabelling with 99m Tc. The changes observed in vivo on comparing the three are very interesting. A seven fold increase in tumour uptake is seen after nanoconjugation highlighting the synergistic effect of active passive targeting resulting in enhanced tumour imaging. This study thus opens up a new area where the nanoplatforms can be designed to get the best of both targeting and potential theranostic applications.